Improving thermal comfort in hot-arid Phoenix, Arizona courtyards: Exploring the cooling benefits of ground surface cover and shade - Unal, Muge; Middel, Ariane (Pergamon-Elsevier Science Ltd, 2025)
Courtyards possess unique geometric features that regulate sun exposure, wind, and humidity in hot climates. This study examines how surface materials and shading affect thermal comfort in courtyards in the hot-arid climate of Phoenix, Arizona, through human-biometeorological observations and microclimate modeling. Three courtyards on Arizona State University's main campus, varying in size, aspect ratio, surface cover, and landscape design, were selected as case studies. The thermal environment of these courtyards was first evaluated for a typical hot and dry summer day in June 2023 using the ENVI-met 5.0.1 microclimate model. On-site measurements of key microclimatic variables, including air temperature (Ta), relative humidity (RH), wind speed (WS), and mean radiant temperature (MRT), were collected using the MaRTy platform to validate the model. Three scenario groups were then developed: the first tested various surface materials (concrete, grass, and water), the second assessed the impact of shade-sail coverage, and the third explored the impact of 3D vegetation configurations (central and bordered planting). In total, 24 scenarios were evaluated based on their effects on thermal comfort, using MRT and Physiological Equivalent Temperature (PET) as key metrics. Statistical analyses, including ANOVA and Tukey's HSD tests, were conducted to compare the spatial differences in thermal exposure and comfort across the scenarios. Additionally, hotspot analysis identified the courtyards most affected by MRT changes. The findings show that shading was the most effective intervention for enhancing thermal comfort, reducing MRT by up to 10 degrees C and PET by 2-3 degrees C during peak hours (14:00 h). Surface materials also played a significant role, with grass cover lowering MRT, while water surfaces, though increasing MRT slightly, improved PET by raising humidity. Vegetation, especially in bordered configurations, enhanced airflow, and improved comfort, proving a promising strategy for optimizing courtyard design.
Keywords: Courtyard design; Microclimate; Marty; Envi-met; Heat mitigation